FLORENTINE TEXT AND INTERTEXT IN D. BROWN'S NOVEL “INFERNO'S” - Тверітінова, Тетяна (SWorldJournal, 2022)
The article examines the Florentine text and intertext in D. Brown's novel “Inferno”. The relationship between Brown's novel and Dante Alighieri's “Divine Comedy” is considered at the level of intertextuality (presence of quotations, allusions, reminiscen